Collaboration in New Product Development - Chhawniwala, Hussain (2013)
As researchers have previously said, due to rapid changing consumer needs, short product life cycle, longer concept-to-production and globalization, companies face intense competition, They always need to be at the peak of innovation, and keep introducing new products to maintain customer satisfaction and their market share. This work presents New Product Development from the point of view of knowledge process as well as Agility. It also, describes why firms need to implement Concurrent Engineering, how Concurrent Engineering can be achieved, what are the challenges. Also, as the organizations strive to achieve optimization, how the concept of Concurrent Engineering has been extended, and hence, not only different functional group, but also supplier’s integration, is necessary to bring the effectiveness in New Product Development process. It also defines how collaboration is achieved by organizations through physical or virtual team integration. Secondary research on how Product Development practices are carried out in Europe, China and UK.